PRESEISMIC ANOMALY OF LF SIGNAL ON THE WAVE PATH JAPAN-KAMCHATKA DURING NOVEMBER-DECEMBER 2004 - Rozhnoi A.A.; Solovieva M.S.; Molchanov O.A.; Chebrov V.; Voropaev V.; Hayakawa M.; Maekawa S.; Biagi P.F. (My University, 2006)
The variations of phase and amplitude of LF signal propagating from the transmitter JJY (40 kHz, Fukushima prefecture, Japan) are analyzed. The receiver is situated in Petropavlovsk-Kamchatski (Russia). The time interval from July1, 2004 till January 24, 2005 is included in the examination. This interval is characterized by quiet seismic conditions up to the beginning of November, but rather strong seismic activity occurs in November and December not far from Hokkaido (Japan) and in the region of northern Kuril Islands. Seismic activity in a zone of sensitivity of our wave paths is determined by three series of earthquakes with M = 5.6–7.1. Nighttime “bay-like” phase and amplitude anomalies of the LF signal begin some days before the first earthquake and continue till the last earthquake of this series (M = 6.2, November 11, 2004). Most strong and obvious anomalies appear in the amplitude of the LF signal. After that, during about one fortnight a period of seismic calm is observed. Then there is a following anomaly of the LF signal before two earthquakes (M = 7.1, 28.11.04 and M = 6.8, 6.12.04). The next LF anomaly is observed before the earthquakes on December, 18 and 21 (M = 5.8 and M = 5.6). During the whole period of seismic activity a significant shift in terminator times is also evident. The spectrum of LF seismo-induced anomalies shows a clear increase for the periods of 10–25 min.